Targeted therapies in hepatocellular carcinoma: past, present, and future - Gujarathi, Rushabh; Franses, Joseph W.; Pillai, Anjana; Liao, Chih-Yi (Frontiers in Oncology, 2024)
Targeted therapies are the mainstay of systemic therapies for patients with advanced, unresectable, or metastatic hepatocellular carcinoma. Several therapeutic targets, such as c-Met, TGF-β, and FGFR, have been evaluated in the past, though results from these clinical studies failed to show clinical benefit. However, these remain important targets for the future with novel targeted agents and strategies. The Wnt/β-catenin signaling pathway, c-Myc oncogene, GPC3, PPT1 are exciting novel targets, among others, currently undergoing evaluation. Through this review, we aim to provide an overview of previously evaluated and potentially novel therapeutic targets and explore their continued relevance in ongoing and future studies for HCC.